2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31193
|View full text |Cite
|
Sign up to set email alerts
|

Using a Flipped Lesson to Improve Information Literacy Outcomes in a First-year Design Class

Abstract: Brianna is the Teaching and Learning librarian at the Colorado School of Mines. She collaborates with faculty to design and implement information literacy throughout the curriculum. Prior to her work at the School of Mines, she was the Engineering and Computer Science librarian at the United States Naval Academy and a contract Reference librarian at the National Defense University. She earned her MLIS from the University of Denver in 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The team found that students successfully used higher quality sources on both assignments following the implementation of the flipped lesson. However, the results for the final report demonstrated less improvement, written 10-12 weeks after the lesson [1].…”
Section: Introductionmentioning
confidence: 89%
“…The team found that students successfully used higher quality sources on both assignments following the implementation of the flipped lesson. However, the results for the final report demonstrated less improvement, written 10-12 weeks after the lesson [1].…”
Section: Introductionmentioning
confidence: 89%